Experimental investigation on heat transfer and pressure drop of internal flow in corrugated tubes. (September 2019) - Andrade, F.; Moita, A.S.; Nikulin, A.; Moreira, A.L.N.; Santos, H.
Highlights: Diabatic and adiabatic friction factor data for two corrugated tubes. Corrugated tubes presented a smoother transition than the smooth tube. Corrugated tubes are more effective under transitional flow regime. The highest heat transfer augmentation occurs at Re  ≈ 2000. Qualitative analysis using high-speed thermography provides important details on the flow. Abstract: The operating conditions of the pre-heater zone of an automotive vehicle waste heat recover heat exchanger occurs in, or close to, the transitional flow regime. For such an application the use of corrugated tubes in a cross flow tube heat exchanger is of particular interest. However, not much work has been done in the transitional flow regime in corrugated tubes where the internal flow changes from laminar to turbulent with heat transfer at high heat fluxes. Therefore, more data is needed. Hence, the main purpose of this work is the characterization of the heat transfer and pressure drop of internal flow in corrugated tubes. To this end an experimental setup was developed and validated for the study of a smooth tube and two corrugated tubes that have an internal diameter of 5.75 mm and a heating length of 0.38 m. The experiments were conducted in laminar, transitional and turbulent regime, with Reynolds numbers in the range from 429 to 6212, under both adiabatic and diabatic flow conditions. The heat flux imposed on the tube wall ranged from 5.5 kW/m 2 to 21.1 kW/m 2 . The flow was hydrodynamically fully developed at test section inlet. The results revealed that the friction factor of the corrugated tubes presented a smoother transition than in the case of the smooth tube, being the diabatic and adiabatic friction factor for the corrugated tubes quite similar from laminar to turbulent regime. The corrugated tubes are more effective under transitional flow regime. The highest heat transfer augmentation occurs at Re  ≈ 2000, specifically, the Nusselt number augmentation ( Nuc / Nus ) increases up to 4.7 for the corrugated tube with helical pitch p  = 6 mm and up to 3.8 for the corrugated tube with p  = 12 mm.